A Spectroscopy Study Of Repeatedly Heated Palm Cooking Oil Using An Open Path Optical Method To Measure The Concentration Of Free Fatty Acid - Wan Farahanana, Wan Muhamat (2022)
Palm oil is a vegetable oil that is extracted from the fruits and seeds of the oil palm tree. Since it includes a significant amount of beta carotene or organic compounds, palm oil is usually reddish in colour. Palm oil contains free fatty acids, which can have negative consequences if used repeatedly. Since the heated temperature differs from that of the original cooking oil, the amount of free fatty acids in the cooking oil increases, causing a shift in the molecules. The colour darkens, the concentration increases, and an unpleasant stench is produced as a result of the heating. The goal of this study to analyse the absorbance spectrum of palm cooking oil that has been cooked repeatedly, to figure out the amount of Free Fatty Acid (FFA) in used palm cooking oil when heated for different periods of time and to analyse other factors that can affect the absorption spectrum of the palm cooking oil. Optical methods that merely used light reflection to analyse this objective. Using a spectrometer apparatus, this method is one of the methods for obtaining accuracy in fatty acid measurement. The results of this analysis led to the development of an optical method for testing the quality of cooking oil that is used frequently, as well as a parameter that can detect the quality of cooking oil for the safety of consumers use cooking oil. Eventually, this method can assist the community in determining the quality of cooking oil used in order to prevent diseases such as cancer, obesity, heart disease, and cholesterol. This is a simple alternative that should be used to educate the people about the dangers of oil that is used repeatedly.